MOLECULAR IDENTIFICATION AND ISOLATION OF CAPNOPHILIC AND MESOPHILIC BIO-EMULSIFIER AND BIO-DEMULSIFIER BACTERIA FROM KHASH MUD VOLCANO: Life Sciences-Biology - YASAMAN PARSIA; MOHAMMAD MEHDI MOTAGHI; JAVID AMINI; MARZIEH DANAEI; JAMSHID FOOLADI; MEHRNAZ SHEIKH HOSSEINI (International Journal of Life Science and Pharma Research, 2022)
About 40 oil fields in Iran (27 oil fields on land and 13 oil fields in the sea) that are mainly located in the south and south west of the country face with severe emulsion problems. This fact shows the need of demulsifiers and emulsifiers usage. Bio- demulsifiers and bio-emulsifiers (usage of microbial biosurfactant) can be widely used in the oil and metallurgical industry, food industry, and textile industry instead of physicochemical methods. In this study, capnophilic and mesophilic bacterial isolates from Khash mud volcano had been purified and incubated on the Plate Count Agar medium (Merck/germany) at 30 ° C, in atmospherer with 10%CO2 for 24-48 h. Bio-emulsifier isolates with β-hemolyse activity were screened. Isolates were inoculated in erlenmeyer flask including a medium with mineral salt solution (0/03 % yeast extract and glucose) with 1% kerosene and incubated at 120 rpm and 30 ° C for 48-72 h. For bio-emulsifier test, each sample vortexed and assessed their stabilizing emulsification capacity(degree 0-4). In bio- demulsifier test, 1 ml from erlenmeyer flasks added into tubes containing stable emulsions of water / diesel and diesel/water and properly vertexed and incubated in 30 ° c for assessed of demulsification degree (0 to 5). The surface tension of superior isolates were measured by Tensiometer (TD1C LAUDA). Among 25 screened isolates,12 and 10 isolates had bio-demulsification(superior isolate was C11) and bio-emulsification activity(Superior isolate was C18), respectively. Amount of surface tension of superior isolates showed to reduce 27.7 mN/m(Bio-demulsifer) and 22.6 mN/m(bio-emulsifier), compared with the control sample, 40.1mN/m, and were identified as Bacillus thuringiensis and Bacillus anthracis strain EFF-G51, respectively.